(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to employ fuzzy logic in building a scale to reveal the creative traits of distinguished students. The research sample consisted of (60) male and female teachers (34) males (26) females from all distinguished schools in Thi-Qar Governorate, two schools, Al-Karrar Secondary School for Distinguished and Secondary School of Al-Zahra for girls were chosen intentionally, due to the nature of the research, the researchers adopted the descriptive approach, to achieve the aims of the research, the researchers built a creative traits scale consisting of (54) items, the validity of the scale was verified and proven, (SPSS) was adopted to extract the results. The results were shown: 1. The use of fuzzy logic in building a scale to reveal the creative traits of distinguished students came largely. 2. There are statistically significant differences at the level of significance (α = 0.05) in the use of fuzzy logic among distinguished students according to gender, where the value of (t) (2.2) and statistical significance of (0.03) in favor of males with mean (2.85), while the mean for females (2.69). In light of the results, the researcher recommends the following: -Using fuzzy logic in different stages. - Create an encouraged reward or an appreciation for distinguished teachers or create an annual competition for the ideal teacher in education, to help them to give continuously and create a spirit of competition among them. - Conducting a field study on the use of fuzzy logic in other educational stages.